The Role of Village Government in Increasing the Potential of the Village to Become an Independent Village - Iswandi, Nadi (PT. Global World Scientific, 2024)
This research was conducted to find out the role of the Wuasa Village government, North Lore subdistrict, and Poso Regency in creating a developed and independent village, as well as the factors that influence it. This type of research is descriptive research with a qualitative approach. Data was collected using field observation, interviews, and documentation methods. The results of this research show that the role of the village government in realizing a developed and independent village in Wuasa Village, Lore Utara subdistrict, Poso Regency, is to process the village's potential well. Village officials collaborate with local communities to cultivate existing village potential.